Pangaroh - Ketua Adat: The Dynamics of Local Leadership of the Dayak Salako Community in Cultural Perspective - Pabali Musa; Diaz Restu Darmawan; Rossa Fitriana; Debora Agustina; Egi Pratama Rizqi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2021)
The phenomenon of the development of the local leadership system in the Dayak Salako community in Nyarumkop village, Singkawang, West Kalimantan, cannot be separated from the current era development; of which the existing leadership system in the community requires dynamic aspects to make the traditional leadership system able to adjust its functions and role in the society that continues to develop. This article will analyze and explain how local leadership forms when community groups Dayak Salako still live as a Bantang community until now, which has become a village community that already has its formal and bureaucratic government leadership. Through a qualitative method with an ethnographic approach, key informants from the customary chief and other stakeholders within the community, it turns out that the leadership of the Dayak Salako customary chief has undergone several changes following the form of life of the community. Even though the global modern development impacts the community's way of life, the importance and influence of customary chief are pertinent.